High titre neutralising antibodies to influenza after oral tablet immunisation: a phase 1, randomised, placebo-controlled trial. Issue 9 (September 2015) - Liebowitz, David; Lindbloom, Jonathan D; Brandl, Jennifer R; Garg, Shaily J; Tucker, Sean N
Summary Background Most influenza vaccines are manufactured in eggs, and the inactivated virus is purified for injection. For a seasonal influenza product, manufacturing, distribution, and perhaps even vaccine coverage, would be greatly improved with an oral tablet alternative made in cell culture. We aimed to assess the safety and immunogenicity of an oral tablet vaccine against influenza A H1N1 in healthy adults. Methods At a single site, we did a randomised, double-blind, placebo-controlled trial of a monovalent influenza A H1N1 vaccine to establish the safety and immunogenicity of a recombinant, non-replicating, adenovirus vector expressing haemagglutinin and double-stranded RNA adjuvant delivered orally by tablets. Participants had to have an initial haemagglutination inhibition titre of at most 1/20, be aged between 18 and 49 years, and be in good health. We randomly assigned (1:1) participants to receive either a single oral dose of vaccine or placebo. Randomisation was done by computer-generated assignment, and study drug was distributed with concealed identity to the masked staff by an unmasked pharmacist. Investigative site staff, people directly involved with immunological assays or the assessment of clinical safety, and participants were masked to treatment assignments. Solicited symptoms of reactogenicity were assessed, and all safety assessments were reported through the active phase of the study (day 28). Immunogenicity was assessed by haemagglutination inhibition titres, the percentage of participants that seroconverted, microneutralisation titres, and the number of antibody secreting cells. Descriptive statistics were used for continuous variables and t-tests or Fisher's exact tests were used to compare treatment groups. The study is registered at ClinicalTrials.gov, number NCT01688297. Findings 24 participants were enrolled in the study at WCCT Global between Dec 2, 2013, and April 15, 2014. Adverse events were mild in nature, and occurred with similar frequency in vaccine (four events) and placebo recipients (four events). After immunisation, 11 (92%) of 12 vaccine-treated participants had a four-fold increase in haemagglutination inhibition titres (group geometric mean fold rise of 7·7) and microneutralisation titres (group geometric mean fold rise of 29). No participants in the placebo group had a four-fold increase in haemagglutination inhibition titres (group geometric mean fold rise of 1·1) or microneutralisation titres (group geometric mean fold rise of 1·0). Neutralising antibody responses to influenza were not hindered by pre-existing immunity to the vector. Interpretation An oral recombinant adenovirus vaccine to influenza was well tolerated and can elicit neutralising antibody responses to influenza virus in human beings. These data are a step forward in making oral influenza vaccination possible. Funding Vaxart Inc.